Enhancing laboratory education through collaborative online international learning: A case study between USA and UK students - Matthew Allan Jones; Pika Miklavc; MaryAnne Stewart (Current Research in Physiology)
Collaborative Online International Learning (COIL) has emerged in recent years as an effective and viable alternative to increase the international opportunities within taught curricula. Through recent innovations in online collaboration tools, and elevated demand for international opportunities, there has been a recent increase in the development of COIL opportunities globally across a range of health aligned disciplines. This style of learning has been described as positively contributing to the internationalisation of students and enhancement of their transferable skills. However, there have been no reported COIL opportunities described in the fields of laboratory medicine and biomedicine, likely due to the large practical elements associated with the subjects. This study therefore aims to develop a COIL opportunity that incorporates practical laboratory elements and evaluate the efficacy of this teaching and learning approach.A laboratory-based COIL was developed and delivered across two days. Day one was composed of synchronous livestreamed laboratory demonstrations and practical activities, with day two focused on the completion of a time-dependent team-based task. The pedagogical impact of this laboratory-based COIL was evaluated through 1) pre and post surveys and 2) an overall survey utilising Likert scales.The laboratory-based COIL was well received by students (n = 34) with the majority enjoying (94.1 %) and learnt a lot (94.1 %) by participating in the session. It also produced highly positive benefits to student confidence (97.1 %), teamworking (100 %), and communication (97.1 %). Pre (n = 46) and Post-analysis (n = 35) revealed significant enhancement of students international education knowledge, international medical practice knowledge, cultural intelligence, social initiative, emotional stability, and work-based flexibility (P < 0.05). Further analysis based on participants international institution revealed significant differences in responses between the two participating cohorts, namely questions relating to cultural intelligence and their confidence of working with cultures unfamiliar to themselves.We are the first to report that implementation of laboratory-based COIL opportunities have significant potential in enhancing students' international, cultural and transferable competencies within laboratory and health education. These findings suggest that practical-based COILs are effective methods for preparing students to thrive in a globalized healthcare environment, making a strong case for its continued use and expansion in educational programmes.